Research activities of the Applied Mechanics group of the University of Genova - Bruzzone, Luca; Carassale, Luigi; Fanghella, Pietro; Verotti, Matteo; Zoppi, Matteo (Anales de Ingeniería Mecánica, 2025)
Within the Italian academic system, the sector of Applied Mechanics (“Meccanica Applicata alle Macchine”) represents one of the engineering disciplines with the most significant historical background. It encompasses scientific, technological, and educational aspects related to the mechanics of machines, both from the perspective of their components and their operation as complex systems. The methodological approaches employed are varied: theoretical, numerical, and experimental. Regarding the educational aspects, the sector of Applied Mechanics is fundamental (characterizing) for Bachelor’s Degrees in Mechanical Engineering (L-9 class) and for Master’s Degrees in Mechanical Engineering (LM-33 class) and Automation Engineering (LM-25 class). Additionally, it is essential for the PhD Degree in Mechanical, Energy, and Management Engineering at the DIME Department of the University of Genova. The professors of the Applied Mechanics group at the University of Genova are actively engaged in research projects funded at the regional, national, European, and industrial levels. Collaborations are ongoing with Stellantis, Ansaldo Energia, Fincantieri, Leonardo, Hitachi, among others. In this context, the Applied Mechanics sector advances both innovative theoretical contributions and experimental studies aimed at practical applications and technology transfer. The research topics are highly interdisciplinary and include: - Modelling, design, prototyping, and control of innovative industrial robotic systems (two robotic lines developed in collaboration with Stellantis are currently operational in final car assembly); - Modelling, design, and prototyping of service robots for inspection, agriculture, and demining; - Modelling and analysis of micromechanical systems, including compliant mechanisms optimized through analytical and numerical approaches; - Dynamic analysis of systems characterized by vibrations, variable contacts and impacts (e.g., gear trains); - Numerical analysis techniques for mechanical and aeromechanical systems; - Definition and application of methodologies for dynamical analysis, model identification, diagnostics, and monitoring of structural integrity (a monitoring system for turbomachinery rotor blades, developed in collaboration with Ansaldo Energia, is currently in use in several plants).